COMPARATIVE EVALUATION OF EFFICACY AND TOLERABILITY OF ORIGINAL AND GENERIC BISOPROLOL IN PATIENTS WITH ARTERIAL HYPERTENSION 1-2 GRADE - S. N. Tolpygina; E. V. Shilova; S. Y. Martsevich (Столичная издательская компания, 2015)
Aim. To study a clinical equivalence of two medications of bisoprolol in patients with arterial hypertension (AH) 1-2 grades. Methods. Efficacy and tolerability of original (Concor, NYCOMED, Merck KGaA) and generic (Bisogamma, WORWAG PHARMA GmbH & Co) bisoprolol were investigated in open-label cross-over randomized comparative study. 32 patients (15 males and 17 females) with AH of 1 (66%) and 2 (34%) grades aged of 60 y.o. on average were involved. After 2 weeks of wash-out period original or generic bisoprolol 5 mg daily was prescribed. If necessary a dose of drug was doubled in two weeks. In patients with significant bradycardia (heart rate <55 bp/min) or atrioventricular block (1-2 degree) hydrochlorothiazide (HCT) 12.5-25 mg per day was added. There was another 2-week wash-out period between two active treatment periods. Results. Systolic and diastolic blood pressure (SBP, DBP) as well as heart rate (HR) were decreased significantly after two weeks of treatment with original bisoprolol (∆SBP=13.8±8.9, ∆DBP=8.5±8.6 mmHg and ∆HR=9.9±13.7 bp/min). Generic medication also significantly reduced SBP, DBP and HR (∆SBP=10.1±10.3, ∆DBP=7.1±7.2 mmHg and ∆HR=9.3±9.4 bp/min). Target SBP/DBP levels were achieved in 62.5%/71.9% of patients in Concor group and in 43.7%/62.5% of patients in Bisogamma group. There was a tendency to additional SBP decrease in patients treated with bisoprolol at a dose of 10 mg and with HCT in Concor group (-5.1±7.4 mmHg; p<0.09) and in Bisogamma group (-5.2±7.9 mmHg; p<0.06). After 4 weeks of treatment target SBP/DBP levels were achieved in 90.1%/96.9% of patients in Concor group and 75%/84.4% patients in Bisogamma group. The investigated parameters did not change significantly in a period between the 4 and 6 weeks of treatment. Monotherapy with Concor and Bisogamma was effective in 84.4% in 62% of patients, respectively (p<0.05). After 6 weeks of treatment target SBP and DBP levels were achieved in 96.9% of patients in the both groups. Average daily doses of original and generic bisoprolol were 6.5 and 7.2 mg, respectively. Conclusion. Generic bisoprolol demonstrated lower antihypertensive efficacy and similar tolerability in comparison with original bisoprolol.